Strategi Kreatif Mengajar Bahasa Inggris Untuk Anak Sekolah Dasar - Nadia Tiara Antik Sari; Alfia Habwah Hendranti; Bunga Aldenina; Deli Setiasari; Dhya Ariz Azizah; Destiana Eka Putri; Fadinda Syifa Faozan; Isna Handayani; Nenden Permas Hikmatunisa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
English Language learning at the Primary School (Elementary) level holds a crucial role in preparing the younger generation to face global challenges (Oktafiah & Laksita, 2023). However, often English learning faces constraints such as monotonous methods, lack of student motivation, and the perception that English is a difficult subject. This study aims to identify and analyze effective creative learning strategies to improve primary school students’ interest, motivation, and basic English Language proficiency, through a qualitative descriptive literature study approach. The creative strategies found emphasized on the creation of a fun, interactive, and child-friendly learning atmosphere, known as fun learning or joyful learning (Ajeng Parnawati & Eka Fajarwati, n.d.). This approach was implemented through a variety of techniques, including the use of educational games (games), role play (role play), songs, and contextualized visual-audio media. The results of the literature study showed that the implementation of creativity and activity-based strategies proved to be effective in increasing the enthusiasm, active participation, as well as vocabulary acquisition and speaking skills of elementary school students(Fredi Daar et al., 2025). This success also depends heavily on the role of teachers as facilitators and demonstrators who are able to develop pedagogical skills and be flexible in modifying lessons according to students’ characteristics.